Analisis Kebangkrutan Dan Ukuran Perusahaan Terhadap Return Saham - Mia, Eni; Sastra, Heri (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
Investments are now much in demand by the public. Various types of investments are being offered, one of them is investment in shares. Investors expect to benefit from the investment. But selecting which stocks worth to buy requires a careful consideration concerning informations about the company’s performance. To obtain such informations, investors may access the financial statements of the company concerned. This study uses research explanation (explanation research) with quantitative approach. This method of research is used to explain the causal relationship between the variables through hypothesis testing, i.e. test hypotheses based on theories that have been formulated beforehand and then the data that has been obtained. This research was conducted by way of explaining the symptoms caused by an object of research. The analysis is partial correlation analysis and multiple linear regression analysis, where the independent variable (X1) is a bankruptcy analysis, the independent variable (X2) is the size of the company and the dependent variable (Y) is the stock return. The results showed that the variables (X1) analysis of bankruptcy does not have a significant effect on stock returns, variable (X2) the size of the company has a significant effect on stock returns. Simultaneously, both independent variables (X1) analysis of the bankruptcy and the independent variable the size of the companies (2) have an influence on stock returns.